THE RIGHTS COMPLIANCE OF PEOPLE WITH SENSORY DISABILITIES PERSPECTIVE OF TAFSIR MAQASHIDI - Zaenal Arifin , Mohamad; Bahrul Hikam , Ahmad; Amin , Muhammad (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
The purpose of this article is to provide greater information on Tafsir Maqashidi's research on the rights of individuals with sensory impairments. persons with sensory disabilities have the right to the same treatment as normal persons in their situation as mukallaf. The descriptive-analytical method is being used in this library research study. Research information relevant to the topic has been gathered from books, journals, fiqh books, and other sources. The findings showed that the major goals (maqashid) of the Al-Qur’anic verses addressing individuals with sensory impairments are to uphold religious precepts, acknowledge their existence in their human capacities, and emphasize the significance of treating them with inclusivity. These services, which are all offered to individuals with sensory impairments, are founded on equality, justice, accountability, and human values. For people with sensory disabilities to participate fully in religious, educational, and social events, accessibility and facilities must be provided. This is how the goals and values expressed in the verses that relate to them are to be implemented. Serving as a prayer leader, leading congregational prayers at the mosque, learning science, having the Al-Qur’an available in braille, and so forth are several instances.